Gender diversity and morphosyntax: An account of singular they. Issue 1 (29th April 2020) - Konnelly, Lex; Cowper, Elizabeth
Abstract : As one of the primary means of constructing gendered identities, language is a matter of central concern to transgender people (Zimman 2018 ). In this paper, we present an analysis of non-binary singular they ; that is, they as used to refer to individuals whose gender identity is not, or is not exclusively, masculine or feminine. Despite singular they 's widespread usage and long history in English, not all speakers judge this most recent innovation to be grammatical, even if they do not object to singular they in quantified, generic, or otherwise gender non-specific contexts, and even if they produce the latter sort of examples natively. We argue that resistance to this new use of they can, at least in part, be attributed to speakers' level of participation in a grammatical change in progress. Further, we propose that this change can be categorized into three distinct stages, with they 's most recent broadening – that is, as a non-binary singular pronoun of reference – dovetailing with wider socio-cultural changes (as well as featural changes beyond the pronominal system) that underscore the difficulty in separating grammatical and social judgements. As we aim to show, linguists from all subdisciplines – both theoretical and applied – are especially well suited to leverage theoretical insights to advocate for trans-affirming language practice.